Профилирование радиально-осевых турбин с использованием современных компьютерных технологий - Русанов, Андрей Викторович; Шатравка, О. И.; Косьянова, А. И. (Eastern-European Journal of Enterprise Technologies, 2009)
The analytical profiling method of the impellers of axial-radical type is represented. Two variants of centripetal turbines designed with the help of the developed method are considered. A numerical study of the suggested constructions was held with the help of software package FlowER. The received results indicate the possibility of using the considered approach for tasks solution of the optimal design of flow parts of the turbine